Macroeconomics of decarbonization strategies of selected global south countries: A systematic review - Emenekwe, Chukwuemeka Chinonso; Okereke, Chukwumerije; Nnamani, Uchenna Alexander; Emodi, Nnaemeka Vincent; Diemuodeke, Ogheneruona Endurance; Anieze, Ethelbert Elochukwu (Frontiers in Environmental Science, 2022)
Global concerns over increasing carbon emissions, climate change, decreasing environmental quality, limited and uneven endowments of fossil fuels, rising energy demand, and volatile oil prices have inspired the move toward global energy system decarbonization. The challenges of achieving ambitious climate targets and sustainable development cannot be solved without the significant efforts of the Global South. Regarding net-zero emissions, the main issue for developing countries is avoiding future emissions from industrialization and lock-in into fossil fuel-intensive technologies. However, achieving strategic and ambitious climate targets in the Global South will require understanding the economic implications of decarbonization. This study’s objective and key contribution are to systematically review and provide a detailed assessment of the literature on decarbonization in the Global South to understand the multi-level economic implications of achieving net-zero emissions in the Global South. The assessment considers four broad themes – investment costs, employment impacts, economic growth, and other macroeconomic impacts (such as consumption, debt level, net savings, income and welfare, and trade balance, among others). Overall, the review finds that energy system decarbonization requires substantial investment outlay. Also, it is linked with job displacement in fossil energy sectors and job creation in green sectors. However, there is no unanimous evidence on net job creation in developing countries. Additionally, the GDP impacts are ambiguous; some studies find future GDP growth impacts, while others find GDP decline impacts of decarbonization scenarios. This paper also provides directions for future research